Model Exploration for Community Satisfaction with E-KTP Service Quality as Mediation - Wahyono, Wahyono; Zakiyah, Nuratun (Dinamika Pendidikan, 2020)
This study aimed to analyze the direct and indirect effects of interpersonal communication, work discipline, and facilities on community satisfaction through service quality. The method in this study used a quantitative approach. The population in this study was the people of Semarang Regency who had submitted services in the form of filing KTPs in sub-districts in Semarang Regency with a total of 756,216 people. The sampling technique was cluster random sampling technique, which was calculated by using the Slovin formula with a total sample of 100 respondents. Data collection methods used questionnaires, observations, and documentation. Data analysis method in this study used path analysis, and a single test with a significance level of 5%. The results of the calculation of the data obtained by the mediation equation were Y1 = 9,737 + 0,366X1 + 0,324X2 + 0,529X3 + 0,768e and the equation model of community satisfaction variable were Y2 = 0,942 + 0,318X1 + 0,531X2 + 0,360 X3 + 0,256 Y1 + 0,662e. The results of this study indicated that interpersonal communication, work discipline, and facilities had a direct effect on community satisfaction, and there was an indirect effect between interpersonal communication, work discipline, and facilities on community satisfaction through service quality.